Assessment of the adequacy of safety barriers to hazards - Sobral, José (2019)
The assessment of safety barriers performance is often achieved through tests or inspections in order to determine their availability or probability of failure on demand (PFD). The ultimate objective of these activities is to observe if the safety barrier is operational and to detect possible hidden failures. However, sometimes due to error in design or changes performed on the installation, the referred safety barrier is not adequate or no longer suitable to face the current level of risk. In the present paper is made a description of safety barriers as important means concerning risky situations and a methodology to evaluate the adequacy of a safety barrier is proposed. This methodology links the safety integrity level of an assessed safety barrier to the probability of occurrence of the hazardous event that it should protect. There is a pre-selection of the classified dangerous undetected safety function failures that will be used to determine the probability of failure on demand (PFD) and the safety barrier adequacy to a specific risk. It will be also possible to estimate the probability of occurrence of a hazardous situation corresponding to the simultaneity of the initiating hazardous event and the safety barrier fault (when a demand occurs).